Cho a, b, c thỏa mãn điều kiện a.b.c = 2005. Chứng minh rằng biểu thức sau không phụ thuộc a, b, c: A = 2005a/ab + 2005a + 2005 + 2005b/bc + 2005b + 2005 + c/ac + c + 1
Câu hỏi:
Cho a, b, c thỏa mãn điều kiện a.b.c = 2005. Chứng minh rằng biểu thức sau không phụ thuộc a, b, c:
A=2005aab+2005a+2005+2005bbc+2005b+2005+cac+c+1A=2005aab+2005a+2005+2005bbc+2005b+2005+cac+c+1
Trả lời:
Lời giải
A=2005aab+2005a+2005+2005bbc+2005b+2005+cac+c+1A=2005aab+2005a+2005+2005bbc+2005b+2005+cac+c+1
=a2bcab+a2bc+abc+bbc+b+abc+cac+c+1=a2bcab+a2bc+abc+bbc+b+abc+cac+c+1
=a2bcab(1+ac+c)+bb(c+1+ac)+cac+c+1=a2bcab(1+ac+c)+bb(c+1+ac)+cac+c+1
=acac+c+1+1ac+c+1+cac+c+1=acac+c+1+1ac+c+1+cac+c+1
=ac+c+1ac+c+1=1=ac+c+1ac+c+1=1.
Vậy biểu thức A không phụ thuộc a, b, c.